Synthesis, structure and thermolysis of oxazagermines and oxazasilines. (25th May 2017) - Dannenberg, F.; Thiele, G.; Dornsiepen, E.; Dehnen, S.; Mehring, M.
Abstract : Nine new oxazasilines and oxazagermines were characterized and two of them were proven to be suitable precursors for porous Ge@C. Abstract : Seven new spirocyclic amido alkoxides of silicon and germanium were synthesized by the reactions of substituted 2-(aminomethyl)phenols with silicon(iv ) and germanium(iv ) chloride, respectively. The spirocyclic compounds1–7 exhibit the general structural motif M[OC6 H3 (CH2 NR 1 )-2-R 2 -4]2 [M = Si, R 1 = Ph, R 2 = H (1 ), Me (2 ), Br (3 ); M = Ge, R 1 = Ph, R 2 = H (4 ), Me (5 ), Br (6 ); M = Ge, R 1 = i-Pr, R 2 = H (7 )]. The use of 2-(ethylamino)benzylalcohol and germanium(iv ) chloride as starting materials afforded the spirocyclic compound Ge[EtNC6 H4 (CH2 O)-2]2 (8 ). The structurally related germylene, germanium(ii )-2-(phenylamidomethyl)phenolate (9 ), was prepared by the reaction of Ge[N(SiMe3 )2 ]2 with 2-(phenylaminomethyl)phenol. The tetravalent compounds were isolated as racemates, with the exception of the spirocyclic germanium compound8, for which the R and the S isomers crystallized separately. The compounds were characterized by single-crystal X-ray diffraction analysis, NMR spectroscopy ( 1 H, 13 C{ 1 H}, 29 Si{ 1 H} for1–3 ), IR spectroscopy, and TGA analysis. Porous Ge@C composites were observed after the carbonization of compounds4–9 under argon. The as-prepared Ge@C materials were analyzed by elemental analysis, nitrogen physisorption measurements, powder X-ray diffraction analysis, Raman spectroscopy, and SEM/EDX analysis.